2011
DOI: 10.1177/097168581101700201
|View full text |Cite
|
Sign up to set email alerts
|

Key Dimensions of Spirit at Work—An Indian Perspective

Abstract: Post-globalization trends have left many people with a sense of insecurity-on both the economic and the employment fronts. Business re-engineering, downsizing, lay-offs, excessive consumerism and greed have altered the rules of the business game. Skewed attention to mere economic criteria in many business organizations, even at the cost of societal and environmental factors, is leading to a sense of hollowness, 'something missing', in the organization and its employees. People are making every attempt to disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…For example, Chawla and Guda (2010), while reviewing different definitions that appear in the literature, identified common themes such as 'sense of community', 'inner life', 'meaningful work' and 'transcendence' as different dimensions of WPS. Srirangarajan and Bhaskar (2011) also noted certain key characteristics of WPS that repeatedly appear in the literature. Based on these characteristics, they shortlisted 15 key dimensions of WPS.Similarly, Petchsawang and Duchon (2009), in their attempt to develop a WPS scale in an Eastern context, found that five different themes -'connection', 'compassion', 'mindfulness', 'meaningful work', and 'transcendence' often surfaced in the WPS literature.…”
Section: Dimensions Of Workplace Spiritualitymentioning
confidence: 86%
“…For example, Chawla and Guda (2010), while reviewing different definitions that appear in the literature, identified common themes such as 'sense of community', 'inner life', 'meaningful work' and 'transcendence' as different dimensions of WPS. Srirangarajan and Bhaskar (2011) also noted certain key characteristics of WPS that repeatedly appear in the literature. Based on these characteristics, they shortlisted 15 key dimensions of WPS.Similarly, Petchsawang and Duchon (2009), in their attempt to develop a WPS scale in an Eastern context, found that five different themes -'connection', 'compassion', 'mindfulness', 'meaningful work', and 'transcendence' often surfaced in the WPS literature.…”
Section: Dimensions Of Workplace Spiritualitymentioning
confidence: 86%
“…The community dimension, as well as the aspect of organisational purpose, has been adopted from Milliman et al (2003) scale which was conceptualised as a sense of community and alignment with the organisational values, respectively. These dimensions of spirituality, namely, meaningful work, sense of community, personal-work values alignment and inner life, are also found to be critical dimensions of the Indian perspective of spirituality at work experience (Srirangarajan & Bhaskar, 2011).…”
Section: Workplace Spiritualitymentioning
confidence: 91%
“…On the other hand, Liu and Robertson (2011) came up with three dimensions -'interconnection with a higher power', 'interconnection with human beings', and 'interconnection with nature and all living things'. Srirangarajan and Bhaskar (2011), while presenting key dimensions of spirituality at work from an Indian (Eastern) perspective, listed 15 different dimensions of WPS. Nonetheless, review of different definitions found in literature suggest that the common dimensions of WPS are 'sense of community', 'inner life', 'meaningful work', 'transcendence', 'compassion', and 'mindfulness'.…”
Section: Workplace Spirituality Dimensionsmentioning
confidence: 99%